Enhancement of inhibitory neurotransmission and inhibition of excitatory mechanisms underlie the anticonvulsant effects of Mallotus oppositifolius - Kennedy Kwami Edem Kukuia; Elvis Ofori Ameyaw; Eric Woode; Priscilla Kolibea Mante; Donatus Wewura Adongo (Wolters Kluwer Medknow Publications, 2016)
Context: Mallotus oppositifolius is a shrub that is used traditionally to treat epilepsy, but its potential has not been scientifically validated. Aims: This study investigated the anticonvulsant properties and possible mechanism of action of the 70% v/v hydroalcoholic extract of the leaves of M. oppositifolius.Materials and Methods: Inprinting control region (ICR) mice (25-30 g) were pretreated with the M. oppositifolius leaf extract (10-100 mg/kg) before administering the respective convulsants (pentylenetetrazole [PTZ], picrotoxin [PTX], strychnine [STR], 4-aminopyridine [4-AP], and pilocarpine). The effect of the extract in maximal electroshock seizure (MES) model was investigated also. Statistical Analysis: Data were presented as mean ± standard error of the mean and were analyzed with one-way analysis of variance (ANOVA) or two-way ANOVA where appropriate with Newman-Keuls or Bonferroni post hoc test respectively. P< 0.05 was considered significant. Results: In both PTX and PTZ test, extract delayed the onset of seizures and reduced the frequency and duration of seizures. In the STR-induced seizure test, the extract significantly delayed the onset of seizures and reduced the duration of seizures. The extract also delayed the onset of clonic and tonic seizures as well as increasing the survival of mice in the 4-AP-induced seizure test. It further reduced the duration of tonic limb extensions in the MES test. In the pilocarpine-induced status epilepticus, the extract significantly delayed the onset of clonic convulsions and reduced the frequency and duration of seizures. Moreover, the anticonvulsant effect of the extract was attenuated by flumazenil, a benzodiazepine/gamma-aminobutyric acid (GABA) receptor antagonist. Conclusion: These findings show that the extract has anticonvulsant effect possible mediated by GABAergic, glycinergic neurotransmission, and potassium channel conductions. It may also be acting by antagonizing muscarinic receptor activation and N-Methyl-D-aspartate receptor activation.